Tanker om min jødiske tipoldefar, der blev kristen teolog - Raahauge, Agnete (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
The article tells the story of Carl Paul Caspari who was born a Jew but did not understand what being Jewish meant until he had read the New Testament and converted to Christianity. Caspari was born in 1814 in the Jewish community of German Dessau. He was born into a modern Jewish family and educated in a reformed Jewish school where he learned German and French as well as geography and history. He began studying oriental languages at the University of Leipzig in 1834. Enlightenment philosophy and rationalism influenced his understanding of scripture, but he soon became absorbed with German Romanticism, which led him to a spiritual crisis. A Christian friend advised him to read the New Testament, and upon doing so he was struck by the historically precise portrait of the Jews in the Acts of the Apostles. He now believed in the credibility of the New Testament and in Jesus Christ as the Messiah. In 1838, Caspari was baptized and began studying at the Faculty of Theology in Leipzig. It was when Caspari converted to Christianity that he truly felt Jewish for the first time and saw a vivid connection in the Old Testament. He believed that the Old Testament contains Messianic prophecies and that it is first and foremost a book of promises. The attestation of God’s promise and His delivery on promises are what connect its many texts. Caspari became a professor specializing in the Old Testament at the University in Kristiania. Besides working with the Old Testament he dedicated his work to proving Grundtvig wrong in his belief that the Bible rests on the shoulders of the apostolic creed. However, later in life Caspari realized that his own struggle against rationalism’s interpretation of the Bible had much in common with that of Grundtvig. They both strongly believed in the promise and faithfulness of God. Caspari came to see that it was God’s promise of a pact that tied together the texts in the Old Testament. At that moment he understood the meaning of being Jewish, implying that being Jewish means expecting that God will keep his promise of realizing the goal that he has created and chosen his people for.